Pengaruh Penerapan Model Belajar Kooperatif Tipe Jigsaw Oleh Guru Pak Dan Budi Pekerti Terhadap Minat Belajar Siswa Di Kelas XI SMK St. Nahanson Parapat Sipoholon Kabupaten Tapanuli Utara - Junita Mesra Wani Simaremare; Jungjungan Simorangkir; Maria Widiastuti (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
The aim of this research is to determine the effect of implementing the jigsaw type cooperative learning model in increasing students' interest in learning in PAK & Characteristics subjects at St. Vocational School. Nahanson Parapat Sipoholon, North Tapanuli Regency, 2022/2023 Academic Year. The research hypothesis is: "There is a positive and significant influence of the jigsaw type cooperative model on the interest in learning PAK & Characteristics of class XI students at St. Vocational School. Nahanson Parapat Sipoholon, North Tapanuli Regency." The population is all students of class XI SMK St. Nahanson Parapat, North Tapanuli Regency, totaling 131 people. The research sample was determined using a purposive sampling technique, namely 25 students in class XI TKJ 2 as the experimental class using the jigsaw type cooperative learning model and class This research method is a quantitative approach with a true experimental design method and a post-test only control group design. The instrument used in this research was a 22 item questionnaire. Research data for the questionnaire was analyzed using the Separated Variance t test formula. From the calculation results, the value of tcount = 3.993 > ttable(α=5%) = 2.064. The tcount value is in the curve area of ​​rejection of H0 and acceptance of Ha. Thus, it can be concluded that the research hypothesis is accepted, meaning that there is a positive and significant influence of the jigsaw type cooperative model on the interest in learning PAK & Characteristics of class XI students at St. Vocational School. Nahanson Parapat Sipoholon, North Tapanuli Regency. Differences in interest in learning PAK & Characteristics of class XI students at SMK St. Nahanson Parapat Sipoholon, North Tapanuli Regency, it is known that the average interest in learning PAK & Characteristics of students using the jigsaw type cooperative learning model is 3.27, higher than the average interest in learning PAK & Characteristics of students using the lecture learning model, namely 2. 87.